2015
DOI: 10.3389/fpsyg.2015.01179
|View full text |Cite
|
Sign up to set email alerts
|

Language control in bilingual language comprehension: evidence from the maze task

Abstract: Most empirical evidence on switch costs is based on bilingual production and interpreted as a result of inhibitory control. It is unclear whether such a top–down control process exists in language switching during comprehension. This study investigates whether a non-lexical switch cost is involved in reading code-switched sentences and its relation to language dominance with cross-script bilingual readers. A maze task is adopted in order to separate top–down inhibitory effects, from lexical effects driven by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 67 publications
(98 reference statements)
3
24
1
Order By: Relevance
“…Shadowing latencies (i.e., the delay between word onset in the original recording and the participant's reproduction of the word) showed that switching from L1 into L2 was more costly than switching from L2 into L1, thereby replicating the pattern observed in Bultena et al's (2015a) self-paced reading study. Both studies showed that switching to the weaker L2 is harder than switching to the dominant L1 (an asymmetry also observed by Wang, 2015), and Bultena et al (2015a;2015b) proposed that intra-sentential switching costs are driven by how quickly representations in a language can be activated. They claim that relative proficiency in the L1 and L2, rather than inhibitory control, underlie intra-sentential switching costs in comprehension.…”
Section: Switching Within Sentences: Behavioral Studiesmentioning
confidence: 82%
See 3 more Smart Citations
“…Shadowing latencies (i.e., the delay between word onset in the original recording and the participant's reproduction of the word) showed that switching from L1 into L2 was more costly than switching from L2 into L1, thereby replicating the pattern observed in Bultena et al's (2015a) self-paced reading study. Both studies showed that switching to the weaker L2 is harder than switching to the dominant L1 (an asymmetry also observed by Wang, 2015), and Bultena et al (2015a;2015b) proposed that intra-sentential switching costs are driven by how quickly representations in a language can be activated. They claim that relative proficiency in the L1 and L2, rather than inhibitory control, underlie intra-sentential switching costs in comprehension.…”
Section: Switching Within Sentences: Behavioral Studiesmentioning
confidence: 82%
“…In an effort to determine the cognitive processes associated with switching within meaningful sentences, recent studies used psycholinguistic methods to study intra-sentential codeswitching in two switching directions (Bultena, Dijkstra, & Van Hell, 2015a;2015b;Dijkstra, Van Hell, & Brenders, 2015;Wang, 2015). For example, Wang (2015) asked English-Chinese bilinguals to perform a maze task (Forster, Guerrera, & Elliot, 2009) in which they have to choose one of two alternative words presented on the computer screen (e.g., "The …. rain/were but/fell clock/silently") in order to move through the sentence (correct selection: "The rain fell silently").…”
Section: Switching Within Sentences: Behavioral Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A vast body of evidence shows that the exogenous requirement to switch languages during word naming or when reading has consequences for language processing, notably in the form of language switching costs (e.g., Altarriba, Kroll, Sholl, & Rayner, 1996;Bultena, Dijkstra, & Van Hell, 2015a;2015b;Costa & Santesteban, 2006;Declerck & Philipp, 2015;Gollan & Ferreira, 2009;Litcofsky & Van Hell, 2017;Meuter & Allport, 1999;Wang, 2015; for a review, see Bobb & Wodniecka, 2013). Switch costs in language production, particularly asymmetric switch costs that are larger into the dominant language, are the hallmark evidence for control accounts and are frequently interpreted as evidence for the inhibition of a previously activated non-target language, typically the L1 (e.g., Abutalebi & Green, 2008;Bobb & Wodniecka, 2013;Green, 1998;Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Meuter & Allport, 1999).…”
mentioning
confidence: 99%